Studi Pendahuluan Fitokimia Tanaman Koleksi Arboretum Legok Pulus Garut - Retty Handayani; Ardi Rustamsyah; Farid Perdana; Setiady Ihsan; Deden Winda Suwandi (Journal of Tropical Pharmacy and Chemistry, 2017)
Arboretrum is a botanical garden which is an open place where there are plants that have been labeled. The purpose of this research is the preliminary study on phytochemical content of secondary metabolite compounds on the leaves of the Legok Pulus Garut arboretum collection plant. the results of the study known twenty-two types of plants contained in Arboretum Garut contain various phytochemical compounds and can be used as collection and research base of medicinal plants. Keywords : arboretum, phytochemicals, secondary metabolites.